2013
DOI: 10.2147/vhrm.s43211
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell count as an indicator of microvascular complications in Chinese patients with type 2 diabetes mellitus

Abstract: BackgroundRheological disorders of red blood cells (RBC) and decreased RBC deformability have been involved in the development of diabetic microangiopathy. However, few studies have evaluated the association of RBC count with microvascular complications in patients with type 2 diabetes mellitus (T2DM). The purpose of this study was to investigate the association of RBC count with microvascular complications in patients with T2DM.MethodsThis study involved 369 patients with T2DM: 243 with one or more microvascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In contrast to this study, a study conducted on Chinese patients with T2DM reported that a decreased RBC count is associated with microvascular complications. 33 Likewise, a study performed in Tobago (Caribbean) reported that RBC count, Hgb concentration, and Hct levels in T2DM patients are lower than in the control group. 34 The possible hypothesis for this difference might be that chronic hyperglycemia causes nonenzymatic glycosylation of RBC membrane proteins leading to accelerated aging of RBCs.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to this study, a study conducted on Chinese patients with T2DM reported that a decreased RBC count is associated with microvascular complications. 33 Likewise, a study performed in Tobago (Caribbean) reported that RBC count, Hgb concentration, and Hct levels in T2DM patients are lower than in the control group. 34 The possible hypothesis for this difference might be that chronic hyperglycemia causes nonenzymatic glycosylation of RBC membrane proteins leading to accelerated aging of RBCs.…”
Section: Discussionmentioning
confidence: 96%
“…Also, the erythrocytes (RBCs) count revealed a significant decrease in patients treated with metformin plus insulin. The decrease in RBCs counts in diabetic patients may be due to RBC membrane protein alterations, a decrease in hemoglobin levels and erythropoietin deficiency (13). Hemoglobin is the major component of erythrocytes; thus, when the HbA1c level is elevated, hyperglycemia may increase the β-sheet structure content of Hb causing it to aggregate which subsequently increases WBV (19).…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells (RBCs) count is a pivotal marker for the ability to recognise diabetic patients at risk of microvascular complications. Lower RBCs counts are, therefore, considered as an independent predictor biomarker of the risk of microvascular complications in T2DM patients (13). Additionally, erythrocytes of diabetic patients aggregate more readily that is obviously enhance whole-blood viscosity (WBV), and adversely influence the microcirculation and finely leading to microangiopathy (14).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a larger number of markers of oxidative stress measured within the same study would provide a more complete picture of oxidative stress and microangiopathy in type 2 diabetes. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%